Volatility transmission and dynamic correlation analysis between developed and emerging European stock markets during sovereign debt crisis - Bein, M. Abdurahman; Tuna, Gülcay (Institute for Economic Forecasting, 2015)
This study empirically examines the impact of the sovereign debt crisis on three Central and Eastern European emerging stock markets (the Czech Republic, Hungary, and Poland will be referred as three CEE). Particular attention is given to volatility transmission and conditional correlation changes in the aftermath of the European crisis against the backdrop of countries which have experienced substantial decline in their equity markets. These countries are known as GIPSI (Greece, Ireland, Portugal, Spain and Italy). In order to compare the conditional correlation and account for indirect transmission, the UK, Germany, and France, also referred to as EU 3, are included. To account for the time-variability of the conditional correlations, a dynamic structure is employed that uses the multivariate DCC model of Engle (2002). In order to gauge the impact of the crisis the data are divided into pre-EU crisis and during/after EU crisis, the results are fourfold. First, with the exception of the Greek market, a significant spillover effect from the GIPSI and EU 3 to the three CEE is noticed. Second, among the three CEE the stock market of Poland has shown a significantly higher level of weighted average conditional correlation as compared to Hungary and the Czech Republic. Third, the EU 3 have a higher level of weighted average correlation as compared to GIPSI and, among the GIPIS countries, Spain and Italy have higher level correlations with three CEE. Fourth, the Greek stock market remains the most volatile out of all the mature markets in the sample but the unconditional and conditional correlations during the sovereign debt crisis are substantially lower with respect to three CEE. © 2015, Institute foe Economic Forecasting. All right reserved.
Keywords: DCC-GARCH; Euro zone crisis; Financial spillover; Interdependence; Local stock return